Gestalt Principles Applied on Visual Identity in Bogor City - Suprayitno Suprayitno (Humaniora, 2017)
This study was a review on the problem of rules of logo design principles used in visual identity in the city of Bogor at random. The purpose of this study was to provide input and a better visual identity approach in accordance with the principles of design. One of the theories used was the theory of Gestalt Max Wertheimer. The theory was used to dissect some examples of visual identity in the area especially the city of Bogor. The research applied qualitative research methods, including data collection in the form of literature study, accompanied by observation and documentation. The results of this research are in the form of suggestions and inputs in designing a visual identity or logo, with applied Gestalt principles as one approach to visual solutions more unique and interesting. So the identity of a brand becomes more memorable.